Liposomal formulations of photosensitizers. (October 2019) - Ghosh, Sanjana; Carter, Kevin A.; Lovell, Jonathan F.
Abstract: Photodynamic therapy (PDT) is a clinical ablation modality to treat cancers and other diseases. PDT involves administration of a photosensitizer, followed by irradiation of target tissue with light. As many photosensitizers are small and hydrophobic, solubilization approaches and nanoscale delivery vehicles have been extensively explored. Liposomes and lipid-based formulations have been used for the past 30 years, and in some cases have been developed into well-defined commercial PDT products. This review provides an overview of common liposomal formulation strategies for photosensitizers for PDT and also photothermal therapy. Furthermore, research efforts have examined the impact of co-loading therapeutic cargo along with photosensitizers within liposomes. Additional recent approaches including imaging, overcoming hypoxia, upconversion and activatable liposomal formulations are discussed.